Isoorientin exerts a protective effect against 6-OHDA-induced neurotoxicity by activating the AMPK/AKT/Nrf2 signalling pathway. Issue 12 (24th November 2020) - Ma, Li; Zhang, Boxi; Liu, Jiahe; Qiao, Chunyu; Liu, Yuanyuan; Li, Shize; Lv, Hongming
Abstract : Parkinson's disease (PD) is a progressive neurodegenerative disorder that is closely associated with oxidative stress. Abstract : Parkinson's disease (PD) is a progressive neurodegenerative disorder that is closely associated with oxidative stress. Nuclear factor erythroid 2 related factor 2 (Nrf2) is a key transcription factor that regulates oxidative stress. Isoorientin (IOT), as a dietary C -glucosyl flavone derived from rooibos tea, cereals and legumes, is thought to possess multiple pharmacological activities; however, the protective effect of IOT against 6-hydroxydopamine (6-OHDA)-induced neurotoxicity in SH-SY5Y cells is still poorly understood. The present study focused on investigating whether IOT could ameliorate neurotoxicity and the underlying mechanisms. Our findings indicated that IOT significantly inhibited neurotoxicity reduced apoptotic cell numbers, reactive oxygen species (ROS) overproduction and mitochondrial membrane potential, and modulated the expression of apoptosis-related proteins, including Bcl-2, Bax and caspase-3, which were induced by 6-OHDA. Moreover, IOT also enhanced the expression of the GCLC, GCLM, HO-1, NQO1 and Trx-1 proteins, which mostly depends on the nuclear translation of Nrf2 and reduced expression of the Keap1 protein. IOT significantly increased the phosphorylation of AMPK, ERK, GSK3β, JNK, PI3K and AKT. In contrast, pretreatment with the inhibitors of AMPK and PI3K/AKT only suppressed the nuclear translocation of Nrf2. In addition, the expression of these proteins was effectively decreased by 6-OHDA, and this effect was reversed by IOT treatment. Importantly, the effect of IOT on improving 6-OHDA induced neurotoxicity was remarkably abrogated by the application of Nrf2 siRNA and, AMPK and PI3K/AKT inhibitors. In summary, IOT might play a protective role against 6-OHDA-induced neurotoxicity by inducing the expression of various antioxidant enzymes via the activation of the AMPK/AKT-Nrf2 signalling pathway.